Sharia Banking Policy: A Critical Study of Government Policies in the Development of Sharia Banks in Indonesia - Miftah, Miftahur Rahman; Moh. Roqib; Khusnul Khotimah; Norhafizah Ahmad (Advances in Humanities and Contemporary Studies, 2024)
Islamic banking in Indonesia has experienced significant development since the establishment of Bank Muamalat Indonesia in 1991. This article examines government policies in supporting the growth of Islamic banking through various regulations, such as Law No. 7/1992 and Law No. 10/1998 which open opportunities for the establishment of Islamic banks and conversion from conventional banks. However, the development of Islamic banks still faces various challenges, including limited public understanding, regulations that are not fully supportive, and the lack of skilled human resources in this sector. This article also highlights the development strategy of Islamic banking which includes improving regulations, expanding networks, improving human resource competence, and socialization activities. The main goal of the development of Islamic banking is to provide banking services in accordance with sharia principles, meet the needs of people who do not accept the concept of interest, and support partnership-based businesses. In the end, consistency in the application of sharia principles and improving service quality is the key to the success of Islamic banking in Indonesia.